HBR's 10 must reads on emotional intelligence - Larkin, Susan; Thomas, James Edward (Ascent Audio, 2022)
In his defining work on emotional intelligence, bestselling author Daniel Goleman found that it is twice as important as other competencies in determining outstanding leadership. If you read (or listen to) nothing else on emotional intelligence, listen to these ten articles by experts in the field. We've combed through hundreds of articles in the Harvard Business Review archive and selected the most important ones to help you boost your emotional skills-and your professional success. This book will inspire you to: monitor and channel your moods and emotions; make smart, empathetic people decisions; manage conflict and regulate emotions within your team; react to tough situations with resilience; better understand your strengths, weaknesses, needs, values, and goals; and develop emotional agility.
Featuring "What Makes a Leader?" by Daniel Goleman. - Online resource; title from title details screen (O'Reilly, viewed November 8, 2022)
Keywords: Emotional intelligence; Work -- Psychological aspects; Intelligence émotionnelle; Travail; Aspect psychologique; Work; Psychological aspects; Audiobooks; Livres audio